Žiemgalos vardas skandinavų runomis - Butkus, Alvydas (Baltistica, 1994)
THE NAME OF SEMIGALLIA IN OLD SCANDINAVIAN RUNIC INSCRIPTIONS There is two rune stones in eastern Middle Sweden, in which the name Semigallia (simkala) is inscripted. They are known as Mervalla stone and Gökstone. So far in Lithuanian linguistic literature we have an evidently wrong interpretation of the Swedish place-names mentioned. The contents of the inscription of the Gökstone is comprehended mistakenly as well. It might be as follows: „Roar, son of Gume, put up this stone for Audar, Slode’s father, and for his own father. He [distributed] gold in Sem[igallia]”. In this stone, however, there are only three runes (by the way, msi- instead of sim-), which are considered to be the beginning of the name Semigallia. Thus because of the lack of the whole word such a consideration is rather doubtful. Besides, there is also a box of the so-called Sigtuna scales with an inscription, informing us that „Djavr got these scales from a man who is from Samland” (or „Semgallen“; in runes af simskun mani). We are not sure about the phonetical value of the root sim- because the rune i might mean not only the diphthongs ei or ai but (more frequently) the vowels i, e. In Swedish linguistic literature the word Semgallen is thought to mean „the low land”. Nevertheless, according to the baltists the etymology of this word might be „the northern land” or „the land to the North”.